FRAMEWORK OF JAWI DIGITAL PALEOGRAPHY: A PRELIMINARY WORK - Khairuddin, Omar; Mohd Sanusi, Azmi (2010)
Paleography is the study of ancient handwritten manuscripts to date the age and to localize ancient and medieval scripts. It also deals with analyzing the development of the letters shape. Ancient Jawi manuscripts are one of the less studied. Nowadays, there are over 7789 known Jawi manuscripts were kept in custody of various libraries in Malaysia. Most of those manuscripts were undated with unknown author and location of origin. This important information can be discovered by analyzing the different type of writing styles and recognizing the manuscript illuminations. In this paper, we discuss the paleographical analysis from the perspective of computer science and propose a general framework for that. This process involves investigation of Arabic influence on the Jawi manuscript writings, establishing the paleographical type of the script, and classification of writing styles based on local and global Jawi image features.